The Relationship Between Emotional Self-efficacy, Sensation Seeking, and the Quality of Child-Parent Relationships With Quality of Life Mediated by High-Risk Sexual Behaviors in Students - Etminan, Farnoosh Sadat; Haji Alizadeh, Kobra; Samavi, Seyed Abdul Wahab (International Clinical Neuroscience Journal, 2021)
Background: Considering the importance of quality of life which is related to various physical, psychological, social, and political dimensions of the individual and the importance of the class which plays a decisive role in forming a successful and healthy society. Also, considering the importance of high-risk behaviors in today’s society and the harm that these behaviors create, five variables of quality of life, type of parent-child relationship and sensation seeking, self-efficacy, and high-risk sexual behaviors have been studied together. Methods: The research method was descriptive-correlational with structural equation modeling (SEM). The statistical population included all male and female undergraduate students of Bandar Abbas Branch of Azad University who were studying in the first semester of the 2018-2019 academic year. 260 people were selected through purposive sampling. The inclusion criteria were being an undergraduate student, conscious satisfaction with the implementation method and research process. Data were gathered by the Child-Parent Relationship Quality Questionnaire (PCRS), Zuckerman Sensation Seeking Scale, Quality of Life Questionnaire, High-Risk Sexual Behaviors Questionnaire and Emotional Self-efficacy Scale. Data were analyzed using structural equations with Amos software, version 8.80. Results: The path coefficient between high-risk sexual behaviors and quality of life was -0.84, which indicates the negative and inverse effect of high-risk sexual behaviors and quality of life. The path coefficient between the quality of the parent-child relationship and high-risk sexual behaviors was -0.86, which indicates the negative and inverse effect of the quality of the parent-child relationship and high-risk sexual behaviors. Conclusion: High-risk sexual behaviors mediate the quality of the parent-child relationship and the quality of life of students.